Analysis Digital Track of Hate Speech on Instagram Using a Forensic Linguistic - Katuuk, Nadia Novernia Cristy; Wantasen, Isnawaty Lydia; Imbang, Djeinnie (Universitas Cokroaminoto Palopo, 2024)
This research investigates the phenomenon of hate speech on social media with data obtained from comments on Instagram posts by Gibran Rakabuming Raka, a public figure and politician who is currently the elected vice president. The study employs a qualitative descriptive method with the observation method and utilizes forensic linguistic theory in investigating hate speech comments. It analyzes five examples of hate speech found in the comment section of his private Instagram account @gibran_rakabuming. The data includes five forms of hate speech on Instagram, covering (1) insulting hate speech, (2) provocative hate speech, (3) inciting hate speech, (4) spreading false news hate speech, and (5) defamation hate speech. These findings underscore the importance of awareness in commenting on social media to avoid hate speech and the need for effective prevention measures to mitigate its negative impact on social media platforms. It highlights the importance of awareness and collective efforts to create a safer and more inclusive digital environment. This research contributes to understanding the dynamics of hate speech in the realm of social media.